Public Policy Theory Analysis of the Distribution of Hajj Pilgrim Quotas in Indonesia - Hasmiyati, Hasmiyati; Ramadhani, Ummu Saad (Al-Bayyinah, 2024)
This study analyzes public policy theories on the distribution of hajj pilgrim quotas in Indonesia. The objectives of the research include discussing in depth the understanding and importance of public policy in the hajj pilgrimage, as well as public policy analysis on the distribution of quotas for pilgrims in Indonesia. The research was carried out in a literature manner with a normative juridical approach through data collection by researching literature materials. From the perspective of public policy theory, the hajj visa policy must be designed with various aspects in mind including social justice, administrative efficiency, and applicable legal principles. The government must strive to optimize quota allocation by considering the needs of the community and the existing service capacity. Good management of the registration and quota distribution system can reduce dissatisfaction among prospective pilgrims and increase public trust in this process. Overall, public policies regarding hajj visas and the distribution of hajj pilgrim quotas in Indonesia must continue to be refined by taking into account feedback from the public and making necessary adjustments to face existing challenges. The government is expected to develop policies that not only meet the principles of justice and efficiency but also pay attention to social and cultural aspects relevant to the implementation of the hajj.